Improving vaccine-related pain, distress or fear in healthy children and adolescents–a systematic search of patient-focused interventions. Issue 11 (2nd November 2018) - Lee, Vivian Y.; Caillaud, Corinne; Fong, Jacqueline; Edwards, Kate M.
ABSTRACT: Objective : The WHO recently highlighted the need for research into potential interventions that can be used to mitigate pain during mass vaccinations, in addition to interventions specific for adolescents. The current review examines the literature on potential interventions that can be used during mass vaccination settings in healthy individuals between the ages of 4 and 15 years old.Methods : Criteria for inclusion were: 1)participants between the ages of 4–15 years, 2)interventions that were patient-focused, 3)vaccinations in healthy individuals, 4)outcome measures to include self-reported pain, fear or distress.Results : Twenty-seven articles were identified with a total of 31 interventions. Eleven interventions used injection-site specific interventions, 17 used patient-led interventions and three used a combination of both site-specific and patient-led interventions.Conclusion : Interventions using coolant and vibration together, as well as a combination of site-specific and patient-led interventions, showed the most consistent effects in reducing self-reported pain, fear or distress.